The growth, location, and structure of industry in Egypt - Barbour, Kenneth Michael (New York : Praeger, 1972)
It Discusses industrialization in Egypt.
Erratum slip inserted.
Includes bibliographical references.
occ 16/01/2019
Loans
Keywords: Industries; Egypt